An Improved Tokamak Sawtooth Benchmark for 3D Nonlinear MHD (Communications in Computational Physics, 2008)
Accurate prediction of the sawtooth cycle [1] is an important test for nonlinear MHD codes. The sawtooth cycle in the CDX-U tokamak [2], chosen becauseits small size and low temperature allow simulation using actual device parameters,has been an important benchmark for the comparison of the M3D [3] and NIMROD [5]codes for the last several years. Successive comparisons have led to improvements andrefinements in both codes. The most recent comparisons show impressive agreementbetween the two codes both on the linear instability and on the details of nonlinearcyclical behavior. These tests are somewhat idealized and do not yet agree quantitatively with the experimentally observed sawtooth period. We expect a second generation of CDX-U sawtooth benchmarks based on an analytically specified equilibrium,with source terms that show greater fidelity to the physical device, to produce betteragreement.